Research, Ethics and Risk in the Authoritarian Field - Glasius, Marlies (Springer Nature, 2018)
research ethics; authoritarian countries; research methodology; research in the authoritarian field; risk and field research; ethics and field research; authoritarianism; advice for field research; research transparency; research methods; mental impact of field research; planning for field research; dangers of field research